PERANAN PERBANKAN SYARIAH DALAM MEMBANTU USAHA KECIL DAN MENENGAH (UKM) AKIBAT KRISIS MULTI DIMENSI DI INDONESIA - Kristianto, Djoko (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2006)
ABSTRACT Require to be revised bank function which not yet shared maximally in assisting difficulty of small entrepreneur to get defrayal or credit for the effort of its. Cause during the time impress that becoming bogey and problem to small entrepreneur is difficult get fresh fund or credit for the defrayal of its effort except that will be told procedure which must be faced by the small entrepreneur tend to circumvent. Very sensible likely if ownership of state to the a bank used to serve and defray small industry economic activity. With expected inwrought strategy of service to small and medium industry in giving of credit expected to earn more directional and zero in on. But seems do not easy to to realize the the dream. Cause in very emulation of this kompetitif many small and medium industry which must vie with big effort This matter represent challenge which must be faced by small and medium industry, because to run the strategy is usually required by the source of energy and fund which by dozens is, the source nya] only owned by big scale effort. On that account in emulation usually small and medium industry party always reside in on the side of less beneficial. On that account problems which handcuffing and hindering economic growth rate shall is immediately finished. In because difficulty get loan from bank operating conventionally, hence needing presumably micro and middle small entrepreneur require to look for defrayal alternative from financial institution or bank which is in management by using Moslem law sistem. Therefore in brief article will be studied by how Moslem law bank role a period to multidimensi crisis in Indonesia. Keywords: Banking Moslem Law, Crisis Multi Dimension, Small And Medium Industry